Why are they not coming back? A single-center follow-up study on oncological women oocyte’s storing for fertility preservation - Immediata, Valentina; Cirillo, Federico; Baggiani, Annamaria; Zanagnolo, Maria Federica; Ronchetti, Camilla; Morenghi, Emanuela; Cesana, Amalia; Specchia, Cristina; Levi-Setti, Paolo Emanuele (Frontiers in Endocrinology, 2022)
Oocyte cryopreservation is a valid option for female cancer patients to preserve fertility. The number of patients undergoing fertility preservation (FP) cycles has increased over the past years. Nevertheless, the rates of patients returning to use their cryopreserved material have shown to be considerably low, ranging from 5-8%, but significant data regarding the reasons of such low return rates are scarce. This study is a single-center follow-up retrospective study evaluating the return rate of oncological women who underwent FP at a tertiary care Fertility Center and assessing the reasons influencing the patients who did not return. Data about patients who returned to attempt pregnancy were retrieved from internal registries. Non-returned patients were assessed with a standardized phone survey investigating: health condition, marital status and family projects, spontaneous conceptions, and the reasons why they had not returned to use their gametes. A univariate analysis between returned and non-returned patients was performed. Of the 397 patients who received counseling about FP, 171 (43.1%) underwent oocyte cryopreservation between 2001 and 2017. Nine (5%) died, and 17 (10%) were lost at follow-up. A total of 20 patients (11.7%) returned and 125 did not. In the non-returned group, 37 (29.6%) did not have a partner, 10 (8%) had a previous spontaneous conception, and 15 (12%) had recurrent malignancy at the time of follow-up. In the univariate analysis, younger age at freezing (31.8±6.2 vs. 35.2±4.7; p 0.018), lack of a partner (p 0.002), type of cancer (other than breast cancer; p 0.024) were the significant factors in the non-returned group. As for the personal reason for not coming back, patients mainly answered as follows: lack of a partner (29, 23.2%), the desire for spontaneous motherhood (24, 19.2%), previous spontaneous pregnancies after FP procedures (16, 12.8%), and still ongoing hormonal therapy for breast cancer (13, 10.4%). All patients confirmed their will to keep the storage of their oocytes. The impact of a cancer diagnosis on a woman’s maternal desire, sentimental status and life priorities should be studied more thoroughly. Studies investigating hormonal therapy suppression in breast cancer patients seeking pregnancy should be encouraged. Clinical Trial NCT05223764